Optimal load shedding using bacteria foraging optimization for loss minimization / Siti Noorasyikin Ahmad Zaini - Ahmad Zaini, Siti Noorasyikin (2007)
This thesis presented on optimal load shedding that had been used as the one of a tool to avoid the voltage instability. The bacterial foraging optimization (BFO) algorithm technique is employed to search the load that should be removed from distribution network.